DEVELOPING STUDENTS’ SPEAKING PERFORMANCE THROUGH MASTERING QUESTION WORDS IN ISLAMIC UNIVERSITY SETTING - Ana Kuliahana; Abdul Gafur Marzuki; Andi Nurfaizah (Bajang Institute, 2024)
This study aims to assess and enhance the speaking performance of students in the English Department at the State Islamic University of Datokarama Palu by using the question-word method. The study, a collaborative classroom action research project, involved two cycles, each involving 22 students. Data were collected through class observations, field notes, a questionnaire, and a speaking test. The study aimed to identify students' speaking abilities based on predetermined success criteria. The findings revealed that incorporating question words into the teaching process significantly increased students' motivation, responsiveness, enthusiasm, and confidence in speaking English. Additionally, this method helped students comprehend the content of questions before responding, allowing them to articulate their ideas more effectively. In the first cycle, only five students (23%) met the success criteria, indicating the need for further intervention. However, by the second cycle, 17 students (77%) achieved the success criteria, demonstrating that the question-word technique effectively enhanced their speaking performance. These results suggest that mastering question words is a valuable strategy for improving students' speaking abilities in English, particularly in an Islamic university context